ARTIFICIAL INTELLIGENCE (AI) IN ENGLISH LANGUAGE TEACHING: OPPORTUNITIES, CHALLENGES AND PEDAGOGICAL IMPLICATIONS - Kadirova Nodira Kamilovna; Alikberova Kamila Adhamovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study examines the integration of artificial intelligence (AI) in English language teaching, focusing on its opportunities, challenges, and pedagogical implications. AI technologies, such as intelligent tutoring systems, chatbots, and automated feedback tools, enable personalized learning, adaptive instruction, and continuous assessment, significantly enhancing learner engagement and autonomy. However, the implementation of AI also presents critical challenges, including ethical concerns related to data privacy, over-reliance on technology, and the potential reduction of human interaction in language learning environments. Additionally, teachers may face difficulties in adapting to AI-driven methodologies due to insufficient training and digital literacy gaps. The study highlights the importance of a balanced pedagogical approach that combines technological innovation with human-centered teaching practices. It concludes that while AI has transformative potential in language education, its effectiveness depends on thoughtful integration, teacher preparedness, and critical evaluation of its impact on learning outcomes.